KONDISI SOSIAL EKONOMI MASYARAKAT PEMOHON PENGUASAAN TANAH DALAM KAWASAN HUTAN DI DESA BUNTOK BARU KECAMATAN TEWEH SELATAN KABUPATEN BARITO UTARA - Kartika Rakhmawati; Udiansyah Udiansyah; Hafizianor Hafizianor (Universitas Lambung Mangkurat, 2020)
The number of poor people in Indonesia is still quite large, especially for residents whose livelihoods are based on agraria sources. People who want to manage forest land should have official management rights in order to support their economy. Therefore, the government through the Ministry of Environment and Forestry formulated a program for people's welfare, namely the Land Utilization Object of Agrarian Reform Program (TORA (Tanah Objek Reforma Agraria)). The/objective of/this study was/to examine the/socio-economic conditions of the people applying for land ownership in the/forest area/and review the implementation/of land tenure in the forest area. Data were analyzed using descriptive methods/and/qualitative methods. The results showed that the community consisted of the most productive age groups with the most male sexes and the most dominant livelihood as a farmer. Education level is moderate and 100% islamic religion. The community economy is still low because people's income is still below the poverty line. Most of the time managing land is <10 years and dominantly managed to become oil palm plantations. Social and cultural societies apply value and cultural norms in the form of mutual cooperation, mutual support, and mutual consultation with maximum length of stay is 20-30 years. Customs that are carried out are Manasai dance, bapapai, pakanan sahur lewu dayak, mitoni and wetonan.Keywords: Conditions, social;, economic; applicant; land tenure